Fragment-derived modulators of an industrial β-glucosidase. Issue 22 (27th November 2020) - Makraki, Eleni; Darby, John F.; Carneiro, Marta G.; Firth, James D.; Heyam, Alex; AB, Eiso; O'Brien, Peter; Siegal, Gregg; Hubbard, Roderick E.
Abstract : A fragment screen of a library of 560 commercially available fragments using a kinetic assay identified a small molecule that increased the activity of the fungal glycoside hydrolase Tr Bgl2. An analogue by catalogue approach and detailed kinetic analysis identified improved compounds that behaved as nonessential activators with up to a 2-fold increase in maximum activation. The compounds did not activate the related bacterial glycoside hydrolase Cc BglA demonstrating specificity. Interestingly, an analogue of the initial fragment inhibits both Tr Bgl2 and Cc BglA, apparently through a mixed-model mechanism. Although it was not possible to determine crystal structures of activator binding to 55 kDa Tr Bgl2, solution NMR experiments demonstrated a specific binding site for the activator. A partial assignment of the NMR spectrum gave the identity of the amino acids at this site, allowing a model for Tr Bgl2 activation to be built. The activator binds at the entrance of the substrate-binding site, generating a productive conformation for the enzyme–substrate complex.